Isolated Desmoid Tumor of Pancreatic Tail with Cyst Formation Diagnosed by Beta-Catenin Immunostaining : A Rare Case Report with Review of Literature - Rao, Ram Nawal (JOP. Journal of the Pancreas, 2013)
Context Isolated pancreatic desmoid tumors with cyst formation are uncommon benign mesenchymal soft tissue tumors, characterized by the dense fibroblastic proliferations with abundant extra-cellular collagen matrix. Intraabdominal desmoid tumor usually involve the mesentery and retroperitoneum and mostly occur in association of familial adenomatous polyposis or Gardner’s syndrome.While desmoid tumors do not metastasize, their advancement can be life threatening due to aggressive local invasion, such as mesentery involvement. Isolated, sporadic pancreatic desmoid tumors have been considered anecdotal, with only 10 cases (cystic area in three cases) described in the literature. To our best of knowledge, this patient is fourth case report displaying cyst formatin in desmoid tumor of pancreatic tail. Case report We herein report a very unusual location of sporadic desmoid tumor involving the pancreatic tail with cystic area diagnosed by Beta-Catenin immunostaining. A 11year-old male presented with painless lump in left hypochondrium of abdomen.The diagnosis of pancreatic adenocarcinoma was suspected preoperatively and the patient underwent a splenopancreatectomy. Histopathologic examination revealed dense fibroblastic proliferation with occasional mitosis suggestive of mesenchymal tumor. The diagnosis of Desmoid tumor was confirmed by positivity of Beta-Catenin immunohistochemical analysis. Conservative treatment was given postoperatively. After ten month follow-up, no recurrence was observed. Conclusion Desmoid tumors are very rare in the tail of pancreas with cystic area and their diagnosis can be difficult, such as in our case where it presented as a solid-cystic lesion. Image: Non-encapsulated tumor with cyst formation.